Manfaat â€œManual Lymph Drainage Vodderâ€ (MLDV) Untuk Mengurangi Udem Pada Fraktur Tulang Paha Dengan Fiksasi Internal (Lembaga Penerbitan Universitas Esa Unggul, 2009)
Background: traffic accident is still being major problem in the world wide including Indonesia. The high number of bone fracture has a correlation with the high number of traffic accident. Fracture of the bone might cause edema. This type of edema is rich of protein. If this edema is not manage accurately, it might risk muscle shortening,Â joint stiff and finally could lead to disability. Objectives : This study is aimed to examine the use of â€œManual Lymph Drainage Vodder (MLDV)â€ in reducing edema for patient with fracture of the femur operated using internal fixation.Â Methods : The subjects of this study were patient at the Prof. Dr. R. Soeharso Orthopedic Hospital with fracture of the femur. These subjects were randomized to intervention or control group. Patients in the intervention group received basic treatment and MLDV while in the control group only received basic treatment. Edema was measure using tape measurement before surgery, the first day after surgery and the third day after surgery. Results: There was a difference in the result of measuring edema between group one and two in the first day after surgery. The average increasing edema in the group two is significantly higher than group one ( p = 0.002). Within three days after surgery both group one and two had reducing edema significantly (p = 0.000 & 0.001). There was a difference in the number of reducing edema between group one and two. Group one had a lower reducing edema than group two, although this differences was not statistically significant (p = 0.62). Conclusion: MLDV that was given preoperatively might reduce edema postoperatively. While MLDV that was given postoperatively might assume to speed the reducing edema.Keywords: MLDV Technique, Edema, Fracture Femur